From Natural Resources to Human Rights - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2018)
Per Magnus Wijkman was the first foreign observer to urge Iceland in print to regulate its fisheries by price. This was in 1975, nine years before the Icelandic fishing quota system came into effect, a system judged discriminatory and unconstitutional by the Supreme Court of Iceland in 1998 (but not in 2000!) as well as by the United Nations Committee on Human Rights in 2007, principally because the advice given by Wijkman and others was not heeded. This paper discusses the human rights aspects of natural resources management in view of the International Covenant on Civil and Political Rights which stipulates the inalienable rights of nations to the rents from their natural resources.
Keywords: Q20; 330; natural resources; human rights